2018
DOI: 10.5933/jkapd.2018.45.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effect on <italic>Streptococcus mutans</italic> in Photodynamic Therapy using Different Light Source

Abstract: In a photodynamic therapy, the difference of antibacterial capacity was compared according to the type of source of light when the same quantity of energy is irradiated. After S. mutans is formed in planktonic state and biofilm state, erythrosine diluted to 40 μM was treated for 3 minutes, and as the type of light source, Halogen, LED, and Plasma arc were used, which were irradiated for 30 seconds, 15 seconds and 9.5 seconds, respectively. After the completion of the experiment, CFU of each experiment arm was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
2
9
0
Order By: Relevance
“…Since the output of the home whitening In our study, aPDT groups showed 95% reduction in planktonic states, whereas in dynamic biofilm state, the reduction rate ranged from 53% to 61%. It is well known that bacteria are considerably more resistant in biofilms than in planktonic cultures [11,21,22]. Although aPDT was less effective in the treatment of bacteria with dense biofilms than in planktonic culture, the difference was less than twofold.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 96%
See 3 more Smart Citations
“…Since the output of the home whitening In our study, aPDT groups showed 95% reduction in planktonic states, whereas in dynamic biofilm state, the reduction rate ranged from 53% to 61%. It is well known that bacteria are considerably more resistant in biofilms than in planktonic cultures [11,21,22]. Although aPDT was less effective in the treatment of bacteria with dense biofilms than in planktonic culture, the difference was less than twofold.…”
Section: Confocal Laser Scanning Microscopymentioning
confidence: 96%
“…In this study, erythrosine (Sigma-Aldrich, St. Louis, MO, USA) was chosen as a photosensitizer. The erythrosine concentration was 20 μM/L and it was prepared in phosphate buffered saline (PBS, pH 7.4), sterilized by filtration, covered in an aluminum foil, and stored at -20°C [11][12][13].…”
Section: Photosensitizer and Light Sourcementioning
confidence: 99%
See 2 more Smart Citations
“…Erythrosine (Sigma-Aldrich, St Louis, MO, USA) was used as the photosensitizer, and the concentration of erythrosine was set as 40 μM, according to previous studies [11]. Erythrosine (molecular weight, 879.86 g/mol) powder was mixed with phosphate-buffered saline (PBS), followed by filter sterilization, to prepare a 1 mM erythrosine stock solution.…”
Section: Photosensitizer and Light Sourcementioning
confidence: 99%